Government, society, and culture in the Roman Empire - Millar, Fergus (Millar, Fergus. Rome, the Greek world, and the East, 2004)
This second volume of the three-volume collection of Fergus Millar's published essays draws together 20 of his classic pieces on the government, society, and culture of the Roman Empire. Every article in Volume 2 addresses the themes of how the Roman Empire worked in practice and what it was like to live under Roman rule.